Identifying the Research Trend of Sport Biomechanics over the Last 20 Years: A Bibliometric Analysis of the Scopus Journal Database - Al Ardha, Muchamad Arif; Nurhasan; Kartiko, Dwi Cahyo; Yang, Chung Bing; Bikalawan, Sauqi Sawa; Rizki, Ainun Zulfikar; Herista, Sevesti Violin Wilujeng (Physical Education Theory and Methodology, 2025)
Background. Sports biomechanics is an important part of coaching and athlete conditioning. The training process can be maximised through the implementation of sports biomechanics. Research related to sports biomechanics has grown significantly in recent years. Objectives. This systematic review study aimed to analyse the development trend of sports biomechanics research over the last 20 years. Materials and Methods. This study used a bibliometric approach and a systematic review of the SCOPUS journal database to analyse research trends in the field of sports biomechanics. Results. Over a period of twenty years, there were 259 studies that met the inclusion criteria. The analysis results showed a significant increase in the number of published studies over time, with a total of 2215 citations and an average of 1237 citations. The research tends to focus on biomechanical principles in the context of sports, with the keyword “Biomechanics” being the most dominant. The terms “Sport Biomechanics”, “Human”, and “Sports” were also identified as frequently occurring keywords in the research. In addition, these studies cover various aspects related to human body movement, including movement analysis, health aspects, and technology applications in sports. Conclusions. This study provides insight into the major developments and focal aspects in sports biomechanics over the past two decades, as well as highlighting the diversity of research subjects within this field.